Pragmatic Abilities of Children with Williams Syndrome: A Longitudinal Examination - John, Angela E.; Dobson, Lauren A.; Thomas, Lauren; Mervis, Carolyn B. (Frontiers in Psychology, 2012)
Prior research has indicated that pragmatics is an area of particular weakness for individuals with Williams syndrome (WS). To further address this aspect of the WS social phenotype, we used an individual differences approach to consider both cross-sectional and longitudinal relations among different pragmatic abilities for 14 children with WS, taking into account individual differences in non-verbal reasoning abilities. We also considered the relations between pragmatic abilities and expressive vocabulary ability. Participants were tested at two time points: as 4-year-olds during a 30-min play session with their mothers (Time 1) and an average of 5.87 years later during a one-on-one conversation with a familiar researcher (Time 2). Children’s intellectual and expressive vocabulary abilities were assessed at both time points. Results indicated that the ability to verbally contribute information beyond what was required in response to a question (ExtendQ) was significantly related to the ability to verbally contribute new information in the absence of a question (ExtendS) both at age 4 years and during primary school. At age 4, both the ability to pair verbalizations with eye contact in triadic interactions (secondary intersubjectivity) and expressive vocabulary ability were related to both ExtendQ and ExtendS. Finally, both ExtendQ and the ability to pair verbalizations with eye contact (intersubjectivity) at age 4 years predicted ExtendQ at age 9–12 years. The theoretical implications of our findings and the importance of early pragmatic language intervention for children who have WS are discussed.